Water Treatment - Elshorbagy, Walid; Kabir Chowdhury, Rezaul (IntechOpen, 2013)
Economic development, population growth, and environmental pollution evolving in many parts of the world are placing great demands on existing resources of fresh water and reflecting a "water crisis". Resource management, efficient utilization of the water resources, and above all water purification are all alternatives to resolve the water crisis. Purification approaches include traditional approaches that have lasted for several centuries without major modifications as well as new innovative approaches. This book covers a number of water quality issues relevant to either improving the existing treatment methods or to new advanced approaches. The book has 15 chapters distributed over four sections titled: [1] Management and Modeling of Treatment Systems, [2] Advanced Treatment Processes, [3] Treatment of Organic-contaminated Water, and [4] Advanced Monitoring Techniques.